2015
DOI: 10.1101/gad.266486.115
|View full text |Cite
|
Sign up to set email alerts
|

The Y3** ncRNA promotes the 3′ end processing of histone mRNAs

Abstract: We demonstrate that the Y3/Y3 * * noncoding RNAs (ncRNAs) bind to the CPSF (cleavage and polyadenylation specificity factor) and that Y3 * * associates with the 3 ′ untranslated region (UTR) of histone pre-mRNAs. The depletion of Y3 * * impairs the 3 ′ end processing of histone premRNAs as well as the formation and protein dynamics of histone locus bodies (HLBs), the site of histone mRNA synthesis and processing. HLB morphology is also disturbed by knockdown of the CPSF but not the U7-snRNP components. In conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…Knockdown of the transcription elongation factors, NELF [40] and pTEF-B [41], as well as of Ars2 [42], a protein that directly interacts with FLASH and is important for cell cycle progression [43], results in small amounts of misprocessing of histone mRNA. Knockdown of a small ncRNA, Ro-RNA Y3*, has a similar effect, resulting in accumulation in read-through RNAs and alteration of HLB structure [44]. These results suggest that proper transcription elongation, together with factors in the HLB, also promotes coupling of processing and termination in mammalian cells.…”
Section: Cell-cycle Regulation Of Histone Mrnasmentioning
confidence: 99%
“…Knockdown of the transcription elongation factors, NELF [40] and pTEF-B [41], as well as of Ars2 [42], a protein that directly interacts with FLASH and is important for cell cycle progression [43], results in small amounts of misprocessing of histone mRNA. Knockdown of a small ncRNA, Ro-RNA Y3*, has a similar effect, resulting in accumulation in read-through RNAs and alteration of HLB structure [44]. These results suggest that proper transcription elongation, together with factors in the HLB, also promotes coupling of processing and termination in mammalian cells.…”
Section: Cell-cycle Regulation Of Histone Mrnasmentioning
confidence: 99%
“…Some polyadenylated core histone mRNAs are produced in small amounts in cultured cells as a result of knockdown of a number of factors (NELF (19), ARS2 (20), chromatin modifiers (21), P-TEFb (21), Y-RNAs (22) and SLBP (23)). These treatments likely result in a perturbation of canonical histone pre-mRNA processing after the stem-loop.…”
Section: Introductionmentioning
confidence: 99%
“…have shown that there is production of some polyadenylated and spliced histone H2B mRNAs when human fibroblasts are differentiated into adipocytes in vitro (24). In some of these studies, the relative proportion of polyadenylated mRNAs and properly processed mRNAs were determined and the amount of polyA+ RNA was very small (<5%) (19,22). In other studies, only increases in polyadenylated histone mRNAs over the very small amounts of polyadenylated histone mRNAs present in control cells was described (21).…”
Section: Introductionmentioning
confidence: 99%
“…112 Functional changes in the HLB during S phase As cells enter S-phase, there are at least two major events that together result in a massive increase in histone mRNA levels: initiation of histone gene transcription in response to activation of Cyclin E/Cdk2 in late G1 and activation of histone premRNA processing. Phosphorylation of NPAT by Cyclin E/ Cdk2 is essential for histone gene transcription, 26,27,34 and may also result in the recruitment of pre-mRNA processing factors to the HLB like Symplekin, 52 thereby activating histone premRNA processing.…”
Section: Knockdown Of Y3mentioning
confidence: 99%